1975
DOI: 10.1073/pnas.72.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a calcium-binding protein as a calcium-dependent regulator of brain adenylate cyclase.

Abstract: An activating factor of adenylate cyclase (EC 4.6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
120
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(126 citation statements)
references
References 19 publications
6
120
0
Order By: Relevance
“…It was, however, quite stable and was stored frozen for periods up to 1 month with no loss of activity. DISCUSSION Brain adenylate cyclase shows a biphasic response to Ca2+ (1)(2)(3)(4)(5) and CDR mediates Ca2+ stimulation of the enzyme (3,(5)(6)(7)(8). Brostrom et al (8) recently proposed that brain cortex contains separate CDR-sensitive and -insensitive forms of adenylate cyclase.…”
Section: Resultsmentioning
confidence: 99%
“…It was, however, quite stable and was stored frozen for periods up to 1 month with no loss of activity. DISCUSSION Brain adenylate cyclase shows a biphasic response to Ca2+ (1)(2)(3)(4)(5) and CDR mediates Ca2+ stimulation of the enzyme (3,(5)(6)(7)(8). Brostrom et al (8) recently proposed that brain cortex contains separate CDR-sensitive and -insensitive forms of adenylate cyclase.…”
Section: Resultsmentioning
confidence: 99%
“…It could be due to activation of adenylate cyclase or to inhibition of cyclic nucleotide phos-phodiesterase, but the latter seems less likely because the phosphodiesterase inhibitor 1-methyl-3-isobutylxanthine potentiates the calcium effect. Because a calcium-dependent regulator protein (calmodulin) has been shown to activate adenylate cyclase of brain (29) and to be present in spermatozoa (30,31), possibly in the acrosomal area (32), the activation of an acrosomal membrane adenylate cyclase (33) by a Ca2+_ calmodulin complex seems possible. The results also suggest that more than one Ca2+-dependent process is responsible for induction of the guinea pig sperm acrosome reaction.…”
Section: Discussionmentioning
confidence: 99%
“…CaM has been demonstrated to regulate cyclic nucleotide metabolism (Brostrom et al, 1975), mitosis, cell cycle progression (Rasmussen & Means, 1989) and phosphorylation of oestrogen receptor (ER) (Migliaccio et al, 1984). It has also been reported that oestrogens influence the synthesis of CaM in the rabbit myometrium (Matsui et al, 1983) and in rat and human uteri (Yoshida et al, 1985).…”
mentioning
confidence: 99%